68Ga-PSMA Uptake in Fibrous Dysplasia. (June 2019) - Reale, Maria Lucia; Buttigliero, Consuelo; Tucci, Marcello; Giardino, Roberto; Poti, Carlo
Abstract : Abstract: Prostate cancer is one of the most common malignancies. Imaging tools play an important role throughout the entire process of the disease. The scenario, however, is going to change. Thanks to a higher sensitivity and specificity, the use of the prostate-specific membrane antigen (PSMA) PET is of increasing importance, particularly at the time of diagnosis and in case of biochemical recurrence. Nevertheless, previous reports have described false-positive findings, as tracer-avid physiological findings or benign processes, potential pitfalls for interpretation of 68 Ga-PSMA PET/CT. Here we report a case of PSMA uptake in a histologically proven fibrous dysplasia.